Spiritual Independence of an Artist’s Personality in Postmodernity - SAENKO, S.R.; VOLKOVA, P.S.; KORTUNOV, V.V.; PUPYSHEVA, E.L. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Using the example of Takeshi Kitano’s film Achilles and the Tortoise, the authors attempt to identify the criteria of artistry by answering the question whether the main character of the film is a true artist or a pathetic copyist. Carrying out a comparative analysis of Mathisu’s paintings and contemporary artworks represented by Paul Klee, Yves Klein, Pete Mondrian, and others, the authors testify both to the interpretation of the source and its reinterpretation. Such experience allows arguing that the character of the film is a creative person who does not lose its value outside the cinema.RESUMEN Utilizando el ejemplo de la película de Takeshi Kitano Aquiles y la tortuga, los autores intentan identificar el criterio del arte respondiendo a la pregunta de si el personaje principal de la película es un verdadero artista o un copista patético. Llevando a cabo un análisis comparativo de las pinturas de Mathisu y las obras de arte contemporáneo representadas por Paul Klee, Yves Klein, Pete Mondrian y otros, los autores dan testimonio tanto de la interpretación de la fuente original como de su reinterpretación. Tal experiencia permite argumentar que el personaje de la película es una persona creativa que no pierde su valor fuera del cine.